Effects of ambient PM2.5 exposure on blood lead levels in residents aged 3 to 79 years in Henan province: a cross-sectional survey in 2017 - 2019 - Siyu YANG; Qiuyan ZHAO; Jie ZHANG; Yongxing WANG; Xiaona YAN; Jing PENG; Shufang ZHANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo study the effect of exposure to airborne particulate matter with an aerodynamic diameter of less than 2.5 μm (PM2.5) on blood lead levels in residents aged 3 to 79 years in Henan province, with the aim of providing valuable insights for the prevention and control of PM2.5 air pollution. MethodsUsing stratified random sampling and a questionnaire designed by the National Institute of Environmental Health of the Chinese Center for Disease Control and Prevention, we conducted face-to-face interviews and blood lead detection among 1 152 urban and rural residents aged 3 to 79 years in 8 districts/counties under the environmental pollution monitoring program in Henan province from December 2017 to January 2019. The PM2.5 concentration of the participant's residence was obtained by matching the latitude and longitude of the home address with the high-resolution, high-quality near-surface air pollutant dataset for China (China High Air Pollutants [CHAP] dataset). The PM2.5 exposure level of the surveyed counties/districts was divided into two levels: high and low. Multiple linear regression model was used to analyze the effect of air PM2.5 exposure on blood lead levels of the participants. ResultsThe median annual average concentration of PM2.5 at the registered home addresses of 1 114 participants was measured to be 64.56 μg/m3, while the median blood lead level was found to be 15.32 μg/L. The results of multiple linear regression analysis showed that the participants living in areas with high exposure to atmospheric PM2.5 had an increased risk of having a high blood lead level (excessive risk [ER] = 26.05%, 95% confidence interval [95%CI]: 18.66% - 33.89%) compared to those living in area with low exposure to atmospheric PM2.5 ; and the increased ER of high blood level fluctuated among the participants of different age groups, with the ERs% (95%CI) of 19.41 (4.61 - 36.31), 28.01 (14.01 - 43.73), 14.89 (1.26 - 30.37), 25.79 (4.17 - 51.90), 35.00 (17.26 - 55.41), and 33.35 (16.58 - 52.54) for the participants aged 3 - 5, 6 - 11, 12 - 18, 19 - 39, 40 - 59, and 60 - 79 years, respectively. ConclusionExposure to ambient PM2.5 has a positive effect on the blood lead levels in the residents aged 3 to 79 years in Henan province and the effect varies among the residents of different ages.